The Effect of Morality, Whistleblowing and Internal Control Systems on Fraud Prevention in Village Fund Management: The Moderating Factor of Leadership Style - Fajran, Muhammad; Rohman, Abdul; Preacyllia, Abellinda (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The purpose of this study is to gather empirical evidence on how civil servant morality, misconduct reporting systems, and internal control systems influence the prevention of fraud in village fund management, with situational leadership style as a moderating variable. This study took a quantitative approach, using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The sample included 329 village officials from Kerinci Regency, Jambi Province, who were chosen using a multistage sampling process. The findings revealed that while whistleblowing had no substantial influence on fraud prevention, village officials' morality and internal control systems did. Although internal control mechanisms had a smaller influence on fraud prevention, situational leadership styles boosted the effectiveness of whistleblowing. This study underlined the need of moral integrity, effective internal control, and flexible leadership styles in preventing fraud in village fund management.